2023
DOI: 10.7759/cureus.33994
|View full text |Cite
|
Sign up to set email alerts
|

Morel-Lavallee Lesion: A Case of Lower Extremity Internal Degloving Injury

Abstract: A 22-year-old female patient was seen in the emergency department with a two-week onset of progressively worsening pain and swelling to the medial aspect of her distal left femur. The patient was involved in an automobile versus pedestrian accident two months prior sustaining superficial swelling, tenderness, and bruising to the affected area. Radiographs revealed soft tissue swelling without osseous abnormalities. Examination of the distal femur region revealed a large, tender, ovoid area of fluctuance with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…In another case reported by Durrani et al, bedside ultrasonography revealed a large anechoic fluid collection in the deep subcutaneous plane with mobile internal echogenic debris. Later, the patient underwent contrast-enhanced CT of the affected lower extremity, demonstrating a fluid collection superficial to the deep fascia of the distal posteromedial left femur, confirming the diagnosis of an MLL [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…In another case reported by Durrani et al, bedside ultrasonography revealed a large anechoic fluid collection in the deep subcutaneous plane with mobile internal echogenic debris. Later, the patient underwent contrast-enhanced CT of the affected lower extremity, demonstrating a fluid collection superficial to the deep fascia of the distal posteromedial left femur, confirming the diagnosis of an MLL [ 14 ].…”
Section: Discussionmentioning
confidence: 99%